Failure Patterns of Recurrence and Metastasis After Intensity-Modulated Radiotherapy in Patients With Nasopharyngeal Carcinoma: Results of a Multicentric Clinical Study - Chen, Sixia; Yang, Dong; Liao, Xueyin; Lu, Ying; Yu, Bin; Xu, Meng; Bin, Ying; Zhou, Pingting; Yang, Zhendong; Liu, Kang; Wang, Rensheng; Zhao, Tingting; et al. (Frontiers in Oncology, 2022)
Purpose This study aimed to explore factors associated with recurrence and metastasis after intensity-modulated radiotherapy (IMRT) in patients with nasopharyngeal carcinoma (NPC) and provide evidence for NPC treatment. Methods We retrospectively analysed the treatment dose and survival outcomes of 645 patients with nasopharyngeal carcinoma without distant metastases treated with IMRT for the first time at three treatment centres in the Guangxi Zhuang Autonomous Region, China, between January 2009 and December 2012. Results There were 9.3% of patients (60/645) had recurrence and 17.5% (113/645) had distant metastasis 5 years after treatment. The 1-year, 3-year and 5-year local recurrence rates were 0.9%, 6.5% and 9.0% respectively. And the 1-year, 3-year and 5-year distant metastasis rates were 3.4%, 10% and 17.2%, respectively. In the 60 patients with recurrence, the in-field, marginal-field, and out-field recurrence rates were 93.3% (56/60), 5.0% (3/60) and 1.7% (1/60), respectively. Recurrence failures occurring within the first three years after treatment accounted for 81.7% (49/60). In the 113 patients with metastasis, the size of the cervical lymph node, the presence of lower cervical lymph node metastasis, the residual cervical lymph node size and the time of residual cervical lymph node complete response (CR) were independent prognostic factors for DMFS (P <0.05). Conclusion Most recurrences occured in the first three years after IMRT. In-field recurrence was the most common pattern for loco-regional failure of NPC treatment. The risk of distant metastasis was positively correlated with higher N stage, lower neck nodal metastasis, larger size of cervical lymph nodes, and longer time to response for residual NPC in cervical adenopathy.